MODELLING OF DEPENDENCY OF THE CONSUMPTION LEVEL ON CONSUMER CREDIT - Мельникова, О. П.; Пономарьова, Т. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
Any financial institution aims to increase its profit during lending and investment activity. In modern conditions of the Ukrainian economy banks aim to expand their credit expansion at the expense of increase of consumer crediting which thereby increases solvent demand for consumer goods and services. The latter stimulates relevant supply which encourages the increase of the GDP and the economical growth of the country as a whole.The main trends in the dynamics of consumer crediting, the income of the population and consumption level were defined in this article. Analysis of statistical data showed that from 2007 to 2017 the tendency of increasing rates of consumer credits reveals essential ups and downs. They are caused by economical and political factors, and, since 2016 there has been a sharp increase of the growth rates reflecting the attempts of the population to diminish the effects of inflation at the expense of increase of consumer credits. That is why the research of the credit expansion of the banks at the expense of consumer crediting on the financial market of Ukraine requires more detailed analysis.During the research particular attention was paid to the analysis of the dependency of the consumption level on consumer credits and the income of the population using statistical methods. It was proven that there was no linear relationship between the consumption level and consumer credits in Ukraine in the years 2007–2017. Two-factor-based econometric model of the dependency of the consumption level on consumer credits and the income of the population of Ukraine was built up and studied. High quality of the constructed model shows that it can be used for forecasting, as well as background for further analysis and optimization of the credit expansion of the banks of Ukraine.